Study on the layout methods of stiffening rings for steel cooling towers. (May 2023) - Song, Guoqing; Zhi, Xudong; Li, Zheng; Fan, Feng; Jin, Xiaofei
Abstract: Stiffening rings are commonly employed as strengthening measures in steel cooling towers. However, studies on reasonable layout methods are lacking. In this study, three layout methods are proposed: the equal-spacing method, the method based on the 1st-order eigenvalue, and the method based on the 1st-order buckled mode shape. Finite element models of steel cooling towers were established considering two tower types (hyperbolic-type and cylinder-frustum-type), three tower heights (120 m, 160 m, and 200 m), three geometric parameters, and two latticed shells (single-layer rectangular and double-layer square pyramid shells). A nonlinear stability analysis of steel cooling towers designed by three layout methods was performed, and the load-bearing capacities of the structures were compared to determine the superiority and inferiority of the three layout methods. The results indicated that double-layer latticed shell steel cooling towers can satisfy the requirements of stable bearing capacity without arranging stiffening rings. The layout method based on the 1st-order buckled mode shape is more suitable than the other two methods for single-layer latticed shell steel cooling towers involving various geometric parameters. It is recommended that this method be used to design the layout of the stiffening rings.